Rim4-seeded stress granules connect temperature sensing to meiotic regulation - Rudian Zhang; Shunjin Li; Wenzhi Feng; Suhong Qian; Akshay John Chellappa; Fei Wang (Nature Communications)
Abstract Meiosis is more vulnerable to heat than mitosis in many species including humans. In Saccharomyces cerevisiae, we discovered that stress granule formation halts meiosis at high temperatures. Meiotic stress granules appear at lower temperatures (33–42 °C) than mitotic stress granules (~46 °C), requiring the meiosis-specific RNA binding protein Rim4. Heat triggers site-specific Rim4 dephosphorylation, causing it to self-assemble into stress granule seeds. These recruit other stress granule components like Pab1 and mRNAs, pausing meiosis. Normally, 14-3-3 proteins block this assembly by binding phosphorylated Rim4. After temperature drops, Hsp104 assists to break down stress granules. Longer stress granule persistence correlates with better recovery, suggesting stress granules might provide temporal insulation for cellular repair processes prior to meiotic resumption.